Increased Risk of Non-communicable Diseases in Urbanized Africans May Be More a Consequence of Increased Energy and Fat Intake Than Low Fiber. (7th June 2021) - Ramabolle, Matsepo; Nesengani, Lucky; Sikhumbule, SK; Swart, Rina; Katsidziria, Leo; Wilson, Annette; O'Keefe, Stephen
Abstract: Objectives: Colon cancer (CRC) is one of the westernized diseases, common in the USA and Europe (>50:100, 000), rare in Africa (<5:100, 000). There is overwhelming evidence that CRC is driven by diet and the low risk in Africans may be attributed to the high fiber content of their traditional diet. (>50g/d vs 10g/d). High fiber increases colonic microbial butyrogenesis, which is strongly anticarcinogenic. There is grave concern that CRC is becoming more common throughout Africa with migration to the cities. We hypothesize that this is due to reduced consumption of fiber with westernization. Methods: Groups of 20 healthy middle aged adults of either sex were compared from urban and rural South Africa, and rural Zimbabwe. A fecal sample was collected from each participant for analysis of fecal short chain fatty acids (SCFA) and the functional microbial gene involved in butyrate synthesis, butyryl CoA: acetate-CoA transferase ( bcoA ) were performed by GC-FID and qPCR, respectively. Dietary information was collected using food frequency and 24-h recall questionnaires. Unpaired Student's t-test for normally distributed parameters and Mann-Whitney U-test for not normally distributed parameters were used for statistical analysis. Results: Surprisingly, fiber intake was not decreased in urban SA and Zimbabweans. In fact, the median dietary fiber intakes of the EH (26g/d) were significantly lower than KH (38g/d) ( P = 0.043). However, food quantities consumed by urban participants was significantly higher for calories, fat and meat. Obesity (BMI > 35) was found in 5 urban SA and only 1 rural SA. Comparison of SCFA between the rural and urban SA groups showed no significant differences. In keeping with this, there was no significant differences in the copies of microbial genes responsible for butyrate synthesis. Conclusions: These results did not support our hypothesis that the increase in CRC with urbanization is due to the loss of the high fiber diet. Alternatively, the increased risk could be related to the higher energy consumption and obesity, and/or the higher fat intake, which increases the microbial synthesis of carcinogenic secondary bile acids. More attention should be given to the quality and quantity of food consumed by urbanized Africans to avoid the otherwise inevitable increase in non-communicable diseases. Funding Sources: Stellenbosch University Rector's Strategic Fund.